Phasor Analytical Model of Non-isolated DC/DC Converter Based on Modular Multilevel Converter for DC Transmission Grids - A. Jamshidi Far; D. Jovcic (Journal of Modern Power Systems and Clean Energy, 2023)
Non-isolated DC/DC converter based on modular multilevel converter (MMC) technology is expected to play an important role in future DC transmission grids. This paper presents a phasor analytical model for this new family of converters which is suitable for a range of studies like DC grid power flow or DC/DC parametric design. The 30th-order phasor model is derived in 3 coordinate frames: zero sequence (DC), fundamental frequency ((<tex>$\pmb{dq}$</tex>)), and double frequency (<tex>$d2q2$</tex>). The second-harmonic current suppression control is included as an option. Additionally, an estimation of the required control signals is presented, and a closed-loop model is developed which facilitates direct calculation of all variables and fast parametric studies. The accuracy of the proposed models is verified against a detailed PSCAD model for a wide range of parameters. The studies illustrate the importance of the second-harmonic components on the model accuracy. Finally, the impact of the converter parameters on the performance is studied, and a basic eigen-value stability analysis is given.